The Role of Large Language Models in Enhancing Cybersecurity Measures: Empirical Evidence from Regional Banking Institutions - Zangana, Hewa Majeed; Mohammed, Harman Salih; Husain, Mamo Muhamad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The rapid advancements in artificial intelligence (AI) and machine learning (ML) have significantly influenced the cybersecurity landscape, particularly in the banking sector, where threats are increasingly sophisticated. Large Language Models (LLMs) such as OpenAI’s GPT-4 and Google’s BERT, offer novel approaches to threat detection, fraud prevention, and automated risk assessment. This paper explores the integration of Large Language Models (LLMs) in cybersecurity frameworks within financial institutions, highlighting their role in real-time anomaly detection, predictive analytics, and intelligent automation of security operations. By leveraging LLMs, banks can enhance their cybersecurity resilience, mitigate cyber threats, and improve regulatory compliance. However, challenges such as data privacy concerns, adversarial attacks, and computational resource demands must be addressed to ensure the secure and ethical deployment of these models. This study provides insights into the current applications, benefits, and limitations of Large Language Models (LLMs) in strengthening cybersecurity measures in the banking sector.